Cover Feature: Amine‐Mediated Domino Reaction of Thioisatins: Synthesis of Benzothiophene‐fused N‐Heterocycles under Catalyst‐Free Conditions (2/2021). Issue 2 (27th January 2021) - Deng, Qingsong; Yu, Aimin; Li, Meitong; Meng, Xiangtai
Abstract : Thioisatin, a neglected multi‐purpose compound, can be used to prepare many kinds of sulfur‐containing heterocyclic compounds. More information can be found in the Full Paper by Prof. Xiangtai Meng et al.